Indications of Preterm Caesarean Section: Experience of 100 Cases at a Tertiary Care Hospital in Bangladesh (Journal of Current and Advance Medical Research, 2021)
Background: Preterm caesarean section is performed for different indication among the pregnant women.Objective: The purpose of the present study was to find out the indications of preterm caesarean section among pregnant women.Methodology: This cross sectional study was conducted in the Department of Obstetric & Gynaecology at Shaheed Ziaur Rahman Medical College Hospital, Bogra, Bangladesh from January 2007 to December 2007 for a period of one year. Women with the gestational age between 32 to 36 completed weeks who were selected for delivery by Caesarean section were selected as study population. All the women of study were assessed on the basis of detailed history, clinical examination, gestational period, history of premature rupture of membranes, any vaginal bleeding and fetal condition.Result: A total number of 100 pregnant women were recruited for this study. In this study most of the pregnant women were in the age group of15 to 20 years which was 40(40.0%) cases followed by the age group of 21 to 25 years which were 20(20.0%) cases. About 43(43.0%) cases were complicated with pregnancy induced hypertension. Almost all of them had indication for immediate caesarean section. Among the group incidence of eclampsia was high which was in 23(23.0%) cases; however, preeclampsia was found in 20(20.0%) cases. Ante partum haemorrhage was reported in 10(10.0%) cases. Pregnant women with premature rupture of membrane (PROM) was found in 14(14.0%) cases; furthermore, PROM with Chorioamnionitis was detected in 5(5.0%) cases. Preterm labour with history of previous caesarean section was given by 5(5.0%) women.Conclusion: In conclusion eclampsia and preeclampsia are the most common indication for preterm caesarean section followed by premature rupture of membrane.Journal of Current and Advance Medical Research, January 2021;8(1):44-48